1985
DOI: 10.1093/jn/115.2.263
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Vitamin E in Rats Fed Graded Levels of Pectin

Abstract: Dietary pectin at levels of 0, 3, 6 and 8% was fed ad libitum to rats for 8 wk to evaluate whether the bioavailability of vitamin E fed at 0.001% of the diet was affected by pectin. Rats fed 3% pectin were not different in any vitamin E parameters from those fed 0% pectin. By the end of the study body weights were significantly lower in the 6 and 8% pectin groups after adjusting for their nonsignificant trend of lower food intake. At wk 8, liver vitamin E levels were reduced in the 6 and 8% pectin group compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Methylcellulose, agar, pectin or wheat bran added to the feed of rats at 10% level had a negative effect on vitamin absorption (Gronowska-Senger et al, 1979). In our laboratory, we found similar effects on the bioavailability of vitamin E in rats fed 8 to 10% pectin (de Lumen et al, 1982;Schaus et al, 1985), and a transient decrease in blood vitamin A or vitamin E after the ingestion of S-20% wheat bran (Omaye and Chow, 1984a, b).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Methylcellulose, agar, pectin or wheat bran added to the feed of rats at 10% level had a negative effect on vitamin absorption (Gronowska-Senger et al, 1979). In our laboratory, we found similar effects on the bioavailability of vitamin E in rats fed 8 to 10% pectin (de Lumen et al, 1982;Schaus et al, 1985), and a transient decrease in blood vitamin A or vitamin E after the ingestion of S-20% wheat bran (Omaye and Chow, 1984a, b).…”
Section: Discussionmentioning
confidence: 57%
“…The bioavailability of vitamin B12 and B6 is less when consumed with dietary fiber (Cullen and Oace, 1978;Leklem et al, 1980) and dietary fiber influences urinary excretion of ascorbic acid (Keltz et al, 1978). Recently, we found that plasma concentrations of vitamin E decreased significantly in rats fed high levels of pectin (deLumen et al, 1982) and some physiological alterations occurred at moderate intake (Schaus et al, 1985). Some transient decreases in plasma lipid-soluble vitamins also were found after rats were fed diets containing 20% wheat bran (Omaye and Chow, 1984a, b).…”
Section: Introductionmentioning
confidence: 99%
“…We feel that the method described has many advantages over other techniques and has applications to a variety of situations. Before development of the method for rat restraint, we found that bioavailability studies could be done by obtaining samples with the same venipuncture method when the rats were anaesthetized with methoxylfurane (Schaus et al, 1985;Omaye & Chow, 1984). However, anaesthetics may affect the results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rats suggested that VE bioavailability was impaired by the presence of pectin (110,111). However, no effect of various fiber types (pectin, guar, alginate, cellulose or wheat bran) were observed on the mean increase of plasma α-tocopherol concentration over 24 h in women (112).…”
Section: Dietary Fibermentioning
confidence: 96%